Rent Seeking - Chakraborty, Shankha (IMF Working Papers; Working Paper ;, 2005)
This paper examines the relationship between rent seeking and economic performance when governments cannot enforce property rights. With imperfect credit markets and a fixed cost of rent seeking, only wealthy agents choose to engage in it, since it enables them to protect their wealth from expropriation. Hence, the level of rent seeking and economic performance are determined by the initial distribution of income and wealth. When individuals also differ in their productivity, not all wealthy agents become rent seekers and the social costs of rent seeking are typically lower. In both cases, multiple equilibria with different levels of rent seeking and production are possible.